2018
DOI: 10.1101/470690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive and quantitative analysis of white and brown adipose tissue by shotgun lipidomics

Abstract: Shotgun lipidomics enables an extensive analysis of lipids from tissues and fluids. Each specimen requires appropriate extraction and processing procedures to ensure good coverage and reproducible quantification of the lipidome. Adipose tissue (AT) has become a research focus with regard to its involvement in obesity-related pathologies.However, the quantification of the AT lipidome is particularly challenging due to the predominance of triacylglycerides, which elicit high ion suppression of the remaining lipi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Previously, obesity-driven global accumulation of longchain PUFA-containing TGs was demonstrated in murine models and human biopsies. [35][36][37][38] Increased activity of the FA elongase Elovl6 was proposed to play a role as a common phenomenon in rodent and human adipose tissue in response to excessive nutrient consumption. 38 This suggests that besides upregulation of total enzymatic FA elongation/desaturation machinery, the generation of specific TG molecular species is regulated during obesity development and opens up the questions of how and why specific lipogenic enzymes generate distinct TG species and what their role is in obesity development.…”
Section: Pufa-containing Tgs Are Specifically Upregulated In Obese Watmentioning
confidence: 99%
“…Previously, obesity-driven global accumulation of longchain PUFA-containing TGs was demonstrated in murine models and human biopsies. [35][36][37][38] Increased activity of the FA elongase Elovl6 was proposed to play a role as a common phenomenon in rodent and human adipose tissue in response to excessive nutrient consumption. 38 This suggests that besides upregulation of total enzymatic FA elongation/desaturation machinery, the generation of specific TG molecular species is regulated during obesity development and opens up the questions of how and why specific lipogenic enzymes generate distinct TG species and what their role is in obesity development.…”
Section: Pufa-containing Tgs Are Specifically Upregulated In Obese Watmentioning
confidence: 99%
“…With this regard, a lipidomic study has revealed a dramatic switch in BAT lipidome toward a WAT‐like lipidome after a high‐fat feeding period of 20 weeks 28 . Regarding SPMs, a recent study has described Lipoxin A4 (LXA 4 ) and SPMs precursors 18‐HEPE, 17‐HDHA, and 15‐HETE among the main contributors to differentiate BAT from WAT fatty acid metabolomic phenotype 29 .…”
Section: Introductionmentioning
confidence: 99%